Braking of a Light‐Driven Molecular Rotary Motor by Chemical Stimuli - van Leeuwen, Thomas; Danowski, Wojciech; Pizzolato, Stefano F.; Štacko, Peter; Wezenberg, Sander J.; Feringa, Ben L. (Chemistry : a European journal, 2018)
Artificial molecular motors hold great promise for application in responsive functional materials as well as to control the properties of biohybrid systems. Herein a strategy is reported to modulate the rotation of light‐driven molecular motors. That is, the rotary speed of a molecular motor, functionalized with a biphenol moiety, could be decreased in situ by non‐covalent substrate binding, as was established by 1H NMR and UV/Vis spectroscopy. These findings constitute an important step in the development of multi‐responsive molecular machinery. The rotation of a light‐driven molecular motor can be controlled reversibly by supramolecular binding of a diamine guest to a biphenol moiety.